αvβ3 integrin-targeted micellar mertansine prodrug effectively inhibits triple-negative breast cancer in vivo - Zhong P (Dove Medical Press, 2017)
Ping Zhong,1,2 Xiaolei Gu,1,2 Ru Cheng,1,2 Chao Deng,1,2 Fenghua Meng,1,2 Zhiyuan Zhong1,2 1Biomedical Polymers Laboratory, 2Jiangsu Key Laboratory of Advanced Functional Polymer Design and Application, College of Chemistry, Chemical Engineering and Materials Science, Soochow University, Suzhou, China Abstract: Antibody-mertansine (DM1) conjugates (AMCs) are among the very few active targeting therapeutics that are approved or clinically investigated for treating various cancers including metastatic breast cancer. However, none of the AMCs are effective for the treatment of triple-negative breast cancers (TNBCs). Here, we show that cRGD-decorated, redox-activatable micellar mertansine prodrug (cRGD-MMP) can effectively target and deliver DM1 to αvβ3 integrin overexpressing MDA-MB-231 TNBC xenografts in nude mice, resulting in potent tumor growth inhibition. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays showed that cRGD-MMP had obvious targetability to MDA-MB-231 cells with a low half-maximal inhibitory concentration (IC50) of 0.18 µM, which was close to that of free DM1 and 2.2-fold lower than that of micellar mertansine prodrug (MMP; nontargeting control). The confocal microscopy studies demonstrated that cRGD-MMP mediated a clearly more efficient cellular uptake and intracellular release of doxorubicin (used as a fluorescent anticancer drug model) in MDA-MB-231 cells. Notably, cRGD-MMP loaded with 1,1'-dioctadecyltetramethyl indotricarbocyanine iodide (DiR; a hydrophobic near-infrared dye) was shown to quickly accumulate in the MDA-MB-231 tumor with strong DiR fluorescence from 2 to 24 h post injection. MMP loaded with DiR could also accumulate in the tumor, although significantly less than cRGD-MMP. The biodistribution studies revealed a high DM1 accumulation of 8.1%ID/g in the tumor for cRGD-MMP at 12 h post injection. The therapeutic results demonstrated that cRGD-MMP effectively suppressed MDA-MB-231 tumor growth at 1.6 mg DM1 equiv./kg without causing noticeable side effects, as shown by little body weight loss and histological analysis. This MMP has appeared as a promising platform for potent treatment of TNBCs. Keywords: breast cancer, reduction-sensitive, drug conjugates, micelles, cRGD